Potensi Beban Pencemaran Nitrogen, Fosfat, Kualitas Air, Status Trofik Dan Stratifikasi Waduk Riam Kanan - Simon S Brahmana; Firdaus Achmad (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2012)
Water of the Riam Kanan reservoir is used for irrigation, the supply of raw water, fishery, and hydro-powered,and transportation, etc. Domestic activities of domestic , agriculture, livestock and gold mining gold in the catchment area of Riam Kanan and acitivity fishery activities in the reservoir could be may degrade its water quality .The objective of this research is to know find out more on the pollution potential from catchment area and fishery activity, the characteristics of water quality , the trophic status and stratification of Riam Kanan reservoir. The research was conducted in May, 2009 and August, 2009. The descriptive study method applied had collected secondary data and water samples for analysed analysis. Evaluation was done based on PP no 82/2001 (Government Regulation no 82/2001) and trophic status according to the criteria stated in KepMen LH No:28/2009. Research results on pollution emission potential in the Riam Kanan Reservoir comprised: total Nitrogen 488 kg/day, and total phosphate 158 kg /day, and BOD 3,394 kg/day respectively. The conclusion of It can be concluded that water quality in the Riam Kanan reservoir suitable is in conformity with the criteria of Class 1 (PP 82/2002). The trophic status throphic was identified in the range of mesotrophic - eutrophic or medium fertile. The Stratification of Riam Kanan reservoir is oligomictic.